2017
DOI: 10.1111/jcmm.13084
|View full text |Cite
|
Sign up to set email alerts
|

DDA1, a novel oncogene, promotes lung cancer progression through regulation of cell cycle

Abstract: Lung cancer is globally widespread and associated with high morbidity and mortality. DDA1 (DET1 and DDB1 associated 1) was first discovered and registered in the GenBank database by our colleagues. DDA1, an evolutionarily conserved gene, might have significant functions. Recent reports have demonstrated that DDA1 is linked to the ubiquitin–proteasome pathway and facilitates the degradation of target proteins. However, the function of DDA1 in lung cancer was previously unknown. This study aimed to investigate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…48 hours post transfection, the transfected H292 and A549 cells were collected and stained with PI for 30 mins. Then Cytomics FC500 flow cytometer (Beckman Coulter) was used to analyze the cell cycle of cells according to the fold of DNA as the previous study indicated [ 23 ]. Each experiment was performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…48 hours post transfection, the transfected H292 and A549 cells were collected and stained with PI for 30 mins. Then Cytomics FC500 flow cytometer (Beckman Coulter) was used to analyze the cell cycle of cells according to the fold of DNA as the previous study indicated [ 23 ]. Each experiment was performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Since cancer is characterized by the deregulation of cell cycle activity that lead to aberrant cell proliferation [32][33], many authors have concluded that cancer can be regarded as a disease of the cell cycle [34]. Previous studies reported that many genes can regulate cell cycles to promote LC cell proliferations [35][36][37][38]. Disappointingly, there is no relevant study about the molecular mechanism of SYNJ2 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…For IHC staining of the xenografts, tumour tissues were fixed, embedded and sectioned (4 μm thick). Immunohistochemistry (IHC) staining for TMA and xenograft tissues was performed in accordance with previous procedures . The following antibodies were used as follows: primary antibody against SEZ6L2 (1:100) or cytochrome C (1:100) (Cell Signaling Technology) was used.…”
Section: Methodsmentioning
confidence: 99%